2021
DOI: 10.1111/jac.12503
|View full text |Cite
|
Sign up to set email alerts
|

Safeners improve early‐stage chilling‐stress tolerance in sorghum

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is a versatile crop that can be cultivated as a grain, forage or bioenergy crop. Sorghum ranks 5th in global cereal crop production and is the 3rd largest cereal produced in the United States (Rao et al., 2019). Animal feed, bioenergy market, and the increase in export to China are key drivers for increased demand for U.S. grain sorghum (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…In general, the germination and seedling stage is the weakest period of plant to abiotic stress. Therefore, the germination and seedling stage is crucial for the establishment of plants ( Song et al, 2008 ; Vennapusa et al, 2021 ). Salt stress has serious influence on root length, especially for hypersensitive improved cultivars ( Ukwatta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the germination and seedling stage is the weakest period of plant to abiotic stress. Therefore, the germination and seedling stage is crucial for the establishment of plants ( Song et al, 2008 ; Vennapusa et al, 2021 ). Salt stress has serious influence on root length, especially for hypersensitive improved cultivars ( Ukwatta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We first hypothesized that tolerant sorghum may show temporal variation at the molecular level in response to temperature stress. To investigate genotype-specific variation resulting from the time of day and temperature stress, we selected sorghum varieties that have previously been shown to exhibit different temperature sensitivities (Chiluwal et al 2020;Vennapusa et al 2021). Heat and cold-susceptible RTx430, heattolerant Macia, and cold-tolerant SC224 were subjected to 1 h heat stress (42°C) or cold stress (10°C) at four different times of the day (ZT1, ZT6, ZT9, and ZT15, Figure 1A), and mRNA-Seq was performed from leaf samples (Supplementary Dataset S1).…”
Section: The Transcriptome Response To Temperature Stress Differs Dep...mentioning
confidence: 99%
“…Previous studies have shown that sorghum (Sorghum bicolor), a C4 cereal crop, can tolerate relatively high temperatures compared to other cereals (Sunoj et al 2017;Chiluwal et al 2020). However, sorghum genotypes with different sensitivities to temperature extremes including heat and cold stress have been identified (Chiluwal et al 2020;Ostmeyer et al 2020;Vennapusa et al 2021). Despite, sorghum known to be relatively tolerant to different abiotic stresses, temperature increases above optimum (32°C) can decrease sorghum yields (Prasad, Bheemanahalli & Jagadish 2017;Tack, Lingenfelser & Jagadish 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are more than 30 kinds of herbicide safeners in common use, including dichloroacetamides, oxime ethers, oxazoles, thiazoles, carboxylic acids, hormones and so forth 10 . Safeners such as fluxofenim, oxabetrinil, naphthalic anhydride (NA), benoxacor, flurazole and GA 3 were commonly used in sorghum fields 11–13 . Most safeners accelerate herbicide metabolism and reduce herbicide phytotoxicity by increasing the expression of genes encoding herbicide‐metabolizing enzymes, such as glutathione S‐transferase (GST), cytochrome P450 monooxygenase (P450), polyphenol oxidase (PPO) and UDP‐glucuronosyltransferase (UGT) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Safeners such as fluxofenim, oxabetrinil, naphthalic anhydride (NA), benoxacor, flurazole and GA 3 were commonly used in sorghum fields. [11][12][13] Most safeners accelerate herbicide metabolism and reduce herbicide phytotoxicity by increasing the expression of genes encoding herbicidemetabolizing enzymes, such as glutathione S-transferase (GST), cytochrome P450 monooxygenase (P450), polyphenol oxidase (PPO) and UDP-glucuronosyltransferase (UGT). 14 Benoxacor and flurazole have been proved to mitigate METinduced phytotoxicity in sorghum by increasing the activity of GST and promoting the conjugation of MET and GSH.…”
Section: Introductionmentioning
confidence: 99%